Growth‐Factor Free Multicomponent Nanocomposite Hydrogels That Stimulate Bone Formation. (16th February 2020) - Okesola, Babatunde O.; Ni, Shilei; Derkus, Burak; Galeano, Carles C.; Hasan, Abshar; Wu, Yuanhao; Ramis, Jopeth; Buttery, Lee; Dawson, Jonathan I.; D'Este, Matteo; Oreffo, Richard O. C.; Eglin, David; et al.
Abstract: Synthetic osteo‐promoting materials that are able to stimulate and accelerate bone formation without the addition of exogenous cells or growth factors represent a major opportunity for an aging world population. A co‐assembling system that integrates hyaluronic acid tyramine (HA‐Tyr ), bioactive peptide amphiphiles (GHK‐Cu 2+ ), and Laponite (Lap ) to engineer hydrogels with physical, mechanical, and biomolecular signals that can be tuned to enhance bone regeneration is reported. The central design element of the multicomponent hydrogels is the integration of self‐assembly and enzyme‐mediated oxidative coupling to optimize structure and mechanical properties in combination with the incorporation of an osteo‐ and angio‐promoting segments to facilitate signaling. Spectroscopic techniques are used to confirm the interplay of orthogonal covalent and supramolecular interactions in multicomponent hydrogel formation. Furthermore, physico‐mechanical characterizations reveal that the multicomponent hydrogels exhibit improved compressive strength, stress relaxation profile, low swelling ratio, and retarded enzymatic degradation compared to the single component hydrogels. Applicability is validated in vitro using human mesenchymal stem cells and human umbilical vein endothelial cells, and in vivo using a rabbit maxillary sinus floor reconstruction model. Animals treated with the HA‐Tyr‐HA‐Tyr‐GHK‐Cu 2+ hydrogels exhibit significantly enhanced bone formation relative to controls including the commercially available Bio‐Oss. Abstract : A multicomponent hydrogel platform that combines oxidative coupling with supramolecular co‐assembly to enable the tunability of physical, mechanical, and biological properties desirable in bone tissue regeneration is reported. The strategy permits the integration of the osteogenic properties of Laponite (Lap), the nanofibrous structure of peptide amphiphiles, the pro‐angiogenic properties of glycyl‐histidyl‐lysine (GHK) peptide, and the instant gelation of tyramine‐modified hyaluronic acid (HA‐Tyr).